2022
DOI: 10.2196/36425
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness of Lung Cancer Screening Using Low-Dose Computed Tomography Based on Start Age and Interval in China: Modeling Study

Abstract: Background Lung cancer is the most commonly diagnosed cancer and the leading cause of cancer-related death in China. The effectiveness of screening for lung cancer has been reported to reduce lung cancer–specific and overall mortality, although the cost-effectiveness, optimal start age, and screening interval remain unclear. Objective This study aimed to assess the cost-effectiveness of lung cancer screening among heavy smokers in China by incorporating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In this modelling study, the Markov model on lung cancer screening that developed by our previous work was used and adapted for the purpose of assessing the potential impact of LDCT screening with and without a PRS from a societal perspective. Important assumptions and the overall structure of the model have been thoroughly described before and in supplementary material [ 19 , 20 ]. Per China guideline for the screening and early detection of lung cancer (2021,Beijing) [ 21 ] recommended, 3 hypothetical cohorts of 10,000 current and former smokers aged 50–74 years old were simulated until death or age 79 years (mean life expectancy in China),named non-screening cohort, LDCT screening cohort and LDCT&PRS screening cohort.…”
Section: Methodsmentioning
confidence: 99%
“…In this modelling study, the Markov model on lung cancer screening that developed by our previous work was used and adapted for the purpose of assessing the potential impact of LDCT screening with and without a PRS from a societal perspective. Important assumptions and the overall structure of the model have been thoroughly described before and in supplementary material [ 19 , 20 ]. Per China guideline for the screening and early detection of lung cancer (2021,Beijing) [ 21 ] recommended, 3 hypothetical cohorts of 10,000 current and former smokers aged 50–74 years old were simulated until death or age 79 years (mean life expectancy in China),named non-screening cohort, LDCT screening cohort and LDCT&PRS screening cohort.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Chinese study by Zhao Z. investigated the cost-effectiveness of lung cancer screening among heavy smokers by incorporating the start age and screening interval [79]. The scholars revealed that a lung cancer screening program in China for heavy smokers using low-dose computed tomography was cost-effective for individuals with smoking habits aged 55-74 years, along with one-time screening for those aged 65-74 years.…”
Section: Yes For Japanmentioning
confidence: 99%
“…Third, risk-stratified screening intervals should be further refined. Despite many studies comparing different screening intervals, only the population as a whole was analyzed, and the focus was on stratification to either annual, biennial, or triennial screening [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%